Analysis of Absortive Capacity and Innovation Capacity Behavior on Business Performance at South Bekasi Coffe Shop - Syahyono Syahyono; Akhtareza Firdaus; M. Al Fikri; Raihan Ramos; Krishna Yudha (Komunitas Dosen Indonesia, 2025)
In recent years, the coffee shop industry has undergone significant transformation. This study aims to analyse the impact of absorptive capacity and innovation capacity on business performance in coffee shops in South Bekasi. Using a quantitative method with a descriptive-analytical design, the study tests a conceptual model based on previous theories, including those by Zahra & George (2002) on absorptive capacity and Crossan (2010) on innovation capacity. The findings indicate that absorptive capacity significantly influences business performance by helping businesses absorb, assimilate, and apply new information. On the other hand, innovation capacity has a positive but insignificant effect on business performance. These results suggest that the combination of absorptive and innovation capacities is critical for improving coffee shop performance, particularly in a competitive market. Practical recommendations include developing absorptive capacity through training, market research, and team collaboration to enhance innovation and its implementation.